Developing a digital archive system for imperial Chinese robe in the Qing Dynasty - Su, Miao; Li, Saiquan; Lu, Yan; Yang, Limei; Duan, Yiting; Xiao, Kaida; Pointer, Michael; Luo, Ming Ronnier; Liu, Xiaoxuan (Frontiers in Neuroscience, 2022)
The digital archive of cultural heritage provides new opportunities for the protection of the cultural heritage and the development of online museums. One of the essential requirements for the digitization is to achieve accurate colour appearance reproduction. Taking the Imperial Chinese robes in the Qing Dynasty as an example , this study aims to develop a digital achieve system to digitize the robes using a high-end imaging system and accurately reproduce their colour properties on a display. Currently, there has been very limited study focused on the colour reproduction of silk fabrics or other textile materials. The conventional colour management process using a traditional colour chart however, may not be suitable for the reproduction of silk fabrics because they have very high gloss. To address this difficulty, a unique ‘Qianlong Palette’ colour chart, consisting of 210 silk fabric samples, has been specifically produced for optimizing the colour reproduction of silk fabrics and a colour image reproduction system has been developed for the digitization and archiving of the clothing fabric for the royal court. Colour characterisation models using both the ‘Qianlong Palette’ colour chart and the traditional colour chart, and different mapping methods, are compared and the model with highest accuracy used in a self-programmed interface for automatically processing textile images in the future. Finally, the digital archive system has been validated using six garments of silk fabric relics. The colour differences after the colour image reproduction are all less than 3.00ΔE*ab, indicating acceptable colour reproduction of the system. The images after colour reproduction have also been evaluated subjectively by experts from the museum and the results are considered satisfactory. Our results show that the newly designed ‘Qianlong Palette’ colour chart exhibits superior performance over the conventional colour chart in effectively predicting the colour of the silk fabrics. The self-programmed graphical user interface for image colour management can serve as a powerful tool to truly reproduce the colour appearance of various silk fabric relics in museums in the future and digitally archive those valuable cultural relics for different uses.